DIGITAL ENTREPRENEURSHIP SEBAGAI PENDORONG DAYA SAING UMKM DI ERA DIGITAL - Syahrani Devi (Smart Education, 2026)
Abstract: Digital transformation has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to enhance competitiveness through the adoption of digital technologies. This study aims to analyze the role of digital entrepreneurship in improving MSME competitiveness in the digital transformation era. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 guidelines. Literature was collected from Google Scholar, Scopus, ScienceDirect, Emerald Insight, SpringerLink, and Taylor & Francis Online, covering publications from 2021 to 2025. Of the 185 articles initially identified, 30 met the inclusion criteria and were selected for analysis. The findings indicate that digital entrepreneurship contributes to MSME competitiveness through digital innovation, digital capability development, market expansion, and business model transformation. In addition to improving operational efficiency and decision-making quality, digital entrepreneurship enables MSMEs to create sustainable competitive advantages. The results also reveal that successful implementation depends on technological readiness, human resource competencies, and digital ecosystem support. This study enriches the digital entrepreneurship literature by explaining the relationship between digital entrepreneurship, digital capabilities, digital innovation, and MSME competitiveness. Keywords: digital entrepreneurship; digital transformation; digital capability; msme competitiveness; systematic literature review Abstrak: Transformasi digital telah menciptakan peluang baru bagi Usaha Mikro, Kecil, dan Menengah (UMKM) untuk meningkatkan daya saing melalui pemanfaatan teknologi digital. Penelitian ini bertujuan menganalisis peran digital entrepreneurship dalam meningkatkan daya saing UMKM di era transformasi digital. Metode yang digunakan adalah Systematic Literature Review (SLR) dengan mengacu pada pedoman PRISMA 2020. Pencarian literatur dilakukan melalui Google Scholar, Scopus, ScienceDirect, Emerald Insight, SpringerLink, dan Taylor & Francis Online terhadap artikel yang dipublikasikan pada periode 2021–2025. Dari 185 artikel yang teridentifikasi, sebanyak 30 artikel memenuhi kriteria inklusi dan dianalisis lebih lanjut. Hasil penelitian menunjukkan bahwa digital entrepreneurship berkontribusi terhadap peningkatan daya saing UMKM melalui penguatan inovasi digital, pengembangan kapabilitas digital, perluasan akses pasar, dan transformasi model bisnis. Selain meningkatkan efisiensi operasional dan kualitas pengambilan keputusan, penerapan kewirausahaan digital juga memungkinkan UMKM menciptakan keunggulan kompetitif yang berkelanjutan. Temuan penelitian menunjukkan bahwa keberhasilan implementasi digital entrepreneurship dipengaruhi oleh kesiapan teknologi, kompetensi sumber daya manusia, dan dukungan ekosistem digital. Penelitian ini memperkaya literatur kewirausahaan digital dengan menjelaskan hubungan antara digital entrepreneurship, kapabilitas digital, inovasi digital, dan daya saing UMKM. Kata kunci: digital entrepreneurship; transformasi digital; kapabilitas digital; daya saing umkm; systematic literature review